2018
DOI: 10.1111/1471-0528.15151
|View full text |Cite
|
Sign up to set email alerts
|

The role of metformin and statins in the incidence of epithelial ovarian cancer in type 2 diabetes: a cohort and nested case–control study

Abstract: No evidence found for metformin or statins reducing the incidence of ovarian cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 30 publications
0
16
1
Order By: Relevance
“…After the study of the finally enrolled 24 articles, two other studies were excluded because the effect size of statin on the incidence or mortality of OC had not been calculated or not been reported in the study and four studies were found as being irrelevant to my research according to the information of the full texts of the articles. Eighteen articles were selected for final analysis, of which ten articles were included for the assessment of the relationship between statin use and the risk of developing OC [ 11 , 12 , 16-18 , 22 , 23 , 32-34 ], and nine articles for the relationship between post-diagnosis statin consumption and OC mortality [ 11 , 13-15 , 19-21 , 35 , 36 ]. It should be noted that Lavie et al study [ 11 ], addressed both the risk of incidence and mortality of from OC ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…After the study of the finally enrolled 24 articles, two other studies were excluded because the effect size of statin on the incidence or mortality of OC had not been calculated or not been reported in the study and four studies were found as being irrelevant to my research according to the information of the full texts of the articles. Eighteen articles were selected for final analysis, of which ten articles were included for the assessment of the relationship between statin use and the risk of developing OC [ 11 , 12 , 16-18 , 22 , 23 , 32-34 ], and nine articles for the relationship between post-diagnosis statin consumption and OC mortality [ 11 , 13-15 , 19-21 , 35 , 36 ]. It should be noted that Lavie et al study [ 11 ], addressed both the risk of incidence and mortality of from OC ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…There were 7,943 cases of OC incidence reported in the included studies. Among the studies included [ 11 , 12 , 16-18 , 22 , 23 , 32-34 ], four studies were cohort studies with total sample size of 428,613 individuals [ 17 , 22 , 33 , 34 ], five studies were case-control with total sample size equal to 82,4891 individuals [ 11 , 12 , 16 , 18 , 32 ] and one was a clinical trial with total sample size equal to 997 individuals [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations